2010
DOI: 10.1007/s12263-010-0179-5
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin synergizes with resveratrol to stimulate the MAPK signaling pathway in human articular chondrocytes in vitro

Abstract: The mitogen-activated protein kinase (MAPK) pathway is stimulated in differentiated chondrocytes and is an important signaling cascade for chondrocyte differentiation and survival. Pro-inflammatory cytokines such as interleukin 1b (IL-1b) play important roles in the pathogenesis of osteoarthritis (OA) and rheumatoid arthritis (RA). In this study, we investigated whether curcumin and resveratrol can synergistically inhibit the catabolic effects of IL-1b, specifically the inhibition of the MAPK and subsequent ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 50 publications
4
72
0
Order By: Relevance
“…SIRT1 has regulatory effects on cell differentiation, proliferation, survival, and organism longevity (47, 54 -56). Furthermore, our laboratory and others have previously reported that resveratrol is an inhibitor of the pro-inflammatory cytokine IL-1␤, highlighting that resveratrol suppressed IL-1␤-induced activation of NF-B and NF-B-dependent gene products (51,57,58). Indeed, we have also shown that resveratrol inhibited IL-1␤-induced apoptosis in tenocytes, and this was linked to changes in the expression of p53, Bax, and caspase-3 (38).…”
Section: Discussionsupporting
confidence: 63%
“…SIRT1 has regulatory effects on cell differentiation, proliferation, survival, and organism longevity (47, 54 -56). Furthermore, our laboratory and others have previously reported that resveratrol is an inhibitor of the pro-inflammatory cytokine IL-1␤, highlighting that resveratrol suppressed IL-1␤-induced activation of NF-B and NF-B-dependent gene products (51,57,58). Indeed, we have also shown that resveratrol inhibited IL-1␤-induced apoptosis in tenocytes, and this was linked to changes in the expression of p53, Bax, and caspase-3 (38).…”
Section: Discussionsupporting
confidence: 63%
“…The erythrocyte suspension was pre-incubated with the three kinds of curcuminoids for 4 h before the glucose was added [1]. After pre-incubation, the two concentrations of glucose were added in different groups, the cell suspension was continually incubated for 20 h in a shaking water bath at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, turmeric has been used in traditional ayurvedic and chinese medicine since 3000 B.C. for treating a wide variety of diseases, including coughs, diabetes, hepatic disorders, rheumatism and various types of cancer [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides the protective effect of these bioactive compounds, their bioavailability through oral delivery system is a great challenge for their potential RA treatment. [86][87][88] …”
Section: Anti-arthritic Effectmentioning
confidence: 99%